Legal Protection Against Fishermen's Settlement Located On The Coastal Borderline Of Bone Regency - Rezky Amalia Syafiin; Farida Pattitingi; Sri Susyanti Nur (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2022)
This study aims to find two problems, namely the implementation of the arrangement of fishermen's settlements located on the coastal border and how is the legal protection for the arrangement of fishermen's settlements in the coastal border of Bone Regency. This research uses empirical legal research. The source of data that will be used in this research is the processing of primary data and secondary data. The form of data analysis used in this research is descriptive. The results of the study illustrate that the implementation of the arrangement of fishermen's settlements in the coastal border line of Lonrae Village is seen from two aspects, namely the legal arrangement and its implementation. In its implementation, it is not in accordance with existing regulations because in Lonrae Village there are settlements in the coastal border area that have existed for a long time. Legal protection focuses on two aspects of protection, namely protection for the community and legal protection for the environment as the main aspect in protecting the environment or ecosystem on the coastal border in Lonrae District and protection for the community after the relocation of settlements as a result of enforcing the rule of law in the regional regulation of Bone Regency regarding Spatial Planning. Region of Bone Regency 2013-2023 and Regional Regulation of Bone Regency concerning Detailed Spatial Planning and Zoning Regulations for Watampone Urban Area 2016-2036.